Theorizing the Process of Leaving a Violent Marriage and Getting a Divorce in Tehran. Issue 3 (February 2021) - Nikparvar, Fatemeh; Stith, Sandra; Myers-Bowman, Karen; Akbarzadeh, Mojgan; Daneshpour, Manijeh
This study utilized qualitative methods to develop a theory regarding the process used by Tehranian women who leave violent marriages to get a divorce. Findings from semistructured, in-depth interviews with nine women in Tehran who left their abusive husbands suggested that there are six stages in this process: "denial, " "using cognitive and internal strategies to save marriage, " "using behavioral and external strategies to save marriage, " "seeking power to end violence, " "preparation to leave marriage, " and "termination" stage. The implications of this study help therapists working with women in Tehran who are living in violent marriages and provide effective prevention and intervention services that are appropriately targeted to the specific needs of Iranian women.